Comment on: "Na-Ion Desalination (NID) Enabled by Na-Blocking Membranes and Symmetric Na-Intercalation: Porous-Electrode Modeling" [J. Electrochem. Soc., 163, A530 (2016)]. Issue 10 (13th August 2016) - Smith, Kyle C.; Dmello, Rylan
Abstract : The relationship between pore-scale velocity and superficial velocity was incorrectly described in the original manuscript [ Journal of the Electrochemical Society, 163 (3) A530–A539 (2016)] and has been corrected here. Two equations in the original manuscript that expressed the superficial velocity contained erroneous factors that have been removed, as well. Further, the equation for membrane polarization presented originally contained a sign error that has been corrected here. In all cases, the results originally presented utilized the correct equations, and therefore no results were affected by these errors. In addition, several technical terms have been updated and their meanings clarified here.